Enhance Fruit Ripening Uniformity and Accelerate the Rutab Stage by Using ATP in ‘Zaghloul’ Dates during the Shelf Life - A. A. Lo’ay (MDPI AG, 2021)
The Rutab date involves a physiological process by which the fruit turns completely ripe. The objective of this study was to research the effect of ATP-treated fruit to improve their biologically active compounds of the Rutab process of the ‘Zagloul’ date during shelf-life. Fruits at full color (red) were dipped in 0, 1, 1.5 mmol L−1 ATP solution for 10 min, and then stored at room temperature (27 ± 1 °C) with a relative humidity of (67 ± 4 RH%) for 12 d. We found that ATP treatment, especially at 1.5 mM, enhances the Rutab stage of date fruit, and certain biologically active compounds such as total phenols and flavonoids, in all ATP treatments compared to untreated fruits. ATP enhanced the loss of tannin compounds in fruit but had no impact on the change in fruit moisture percentage of fruit during storage. The treatments did affect the changes in total sugar content and activated the sucrose enzymes, i.e., acid invertase (AI), neutral invertase (NI), sucrose synthase-cleavage (SS-c), and sucrose synthase-synthesis (SS-s) during storage. Interestingly, immersion in 1.5 mM ATP forced the date fruit to reach the Rutab stage during storage. These results indicated that the dose of ATP (1.5 mM) is a new potential tool that pushes the fruits to regular ripening after harvest, thus reducing the losses in the fruits during the production process. A linear model could be satisfactorily used for predicting the properties of the treated date with ATP 1.5 mM at different shelf-life durations.